Formulation and evaluation of modified release Ibuprofen suppositories - صهيوني خزامى; تميم حماد; وهاد إبراهيم (Latakia University Journal -Medical Sciences Series, 2024)
This research aims to study the effect of various molecular weights of PEGs bases, Tween 80 and it is concentration on the release of ibuprofen from modified release suppositories. Several formulations of modified release suppositories were prepared using PEGs (PEG 1500, PEG 1500:4000 3:1) as soluble bases. Tween 80 was added to PEGs suppositories with various concentration (1,3,5) %. The different properties of suppositories were evaluated. The effect of the molecular weights of PEGs, effect of Tween 80 with concentration (1,3,5) % on the release of modified release ibuprofen suppositories were studied. The results show that the released percentage of ibuprofen decreased by increasing the molecular weights of PEGs. Addition of non - ionic surfactant (Tween 80) has a significant effect on the release of ibuprofen; the released percentage increased from formulas containing Tween 80, and the release increased by increasing the concentration of Tween 80 from 1% to 5%.